Multiscale analysis of the unusually complex muscle fibers for the chiton radulae - Sun, Dawei; Liu, Chuang; Wang, Zhenglu; Huang, Jingliang (Frontiers in Marine Science, 2023)
Chiton teeth in the radula are one of the hardest biomaterials in nature. Chiton uses radula to scrape algae on hard surfaces. The ultrastructure and composition of teeth are well known while how they move is less clear. This study used an array of material characterizations including soft-tissue micro-computed tomography (micro-CT), histology, scanning electron microscopy, and proteomics to investigate the tissue that may control the movement of the radula of Acanthopleura loochooana. Surprisingly, unusually complex muscle fibers were found around the radula. 54 muscle fibers with diameters of around 130 µm were anchored to the second and third shell plates. These muscle fibers are in close contact with the radula and cartilage beneath the radula. Proteomics using a recently published chiton genome as a reference confirmed the proteins related to energy metabolism, calcium metabolism, as well as a cartilage oligomeric matrix protein in the muscle. qPCR found that the above proteins were highly expressed in the radula muscle compared to the foot. Taken together, this study provides insights into the complex tissue structures that control the movement of the radula, which may inspire robotics design relating to hard-soft tissue interfaces.